2022
DOI: 10.1002/slct.202203874
|View full text |Cite
|
Sign up to set email alerts
|

Highly effective palladium nanocatalyst supported in polymeric networks for the catalytic hydrogen generation from borane‐morpholine complex

Abstract: This study describes the synthesis of Pd 0 nanoparticles supported in hydrogel networks (SPVI@Pd) and their catalytic activity for the borane-morpholine complex (MB) hydrolysis reaction. In this respect, while our study is one of the limited number of studies reported for the catalytic hydrolysis of MB, it is the first study in which Pd 0 nanoparticles supported in hydrogel networks were used in the catalytic hydrolysis of MB. The synthesized Pd 0 nanoparticles were characterized using structural and morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In another recent study, Ozay et al. reported that SPVI@Pd nanocatalyst provided a TOF value of 187.8 h −1 (303 K) in the MB hydrolysis reaction [19] …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In another recent study, Ozay et al. reported that SPVI@Pd nanocatalyst provided a TOF value of 187.8 h −1 (303 K) in the MB hydrolysis reaction [19] …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MB can be utilized as one of the most reliable chemical H 2 storage materials thanks to its advantages like relatively high H 2 content, low cost, and low toxicity [17] . MB, a white solid with a melting point of 371 K, has received much attention due to its high H 2 content (12 % by weight), which exceeds the Department of Energy's (DOE) 2023 target [18,19] . Although MB has these unique properties, only few studies on H 2 production from MB can be found in the literature [15] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, synthesis in the presence of any support material or stabilizing agent is generally preferred to preserve nanoscale properties. [8] Inorganic oxides, [9,10] fly-ash particles, [11] polymeric particles, [12] hydrogels [13][14][15][16][17] and water-soluble polymers [18] can be counted among the materials that are frequently preferred as stabilizer/ support materials in the synthesis of metallic nanoparticles. The most common metallic nanoparticles in nanobiotechnology are gold and silver nanoparticles.…”
Section: Introductionmentioning
confidence: 99%